The Spirit of Bacon: Science and Self-Perception in the Hudson's Bay Company, 1830-1870 - Zeller, Suzanne (Scientia Canadensis, 1989)
ABSTRACTThis article considers in terms of its larger historical context the participation by officers of the Hudson's Bay Company in the social networks of Victorian science, mainly in the collection of specimens of natural history in the vast northwestern territories of North America. While such specimens were solicited by outsiders from British and American scientific institutions, a common cultural heritage gave meaning and value to the cooperative efforts of both scientists and collectors. A sketch of this heritage, in which the writings of Sir Francis Bacon, the voyages of Captain James Cook, the example of Alexander von Humboldt, the scholarship of the Scottish Enlightenment and other factors were alloyed to form the matrix of Victorian scientific activity, forms the focus of the discussion of both the Company's policies and individual initiatives.